EVALUASI PROGRAM PESANTREN KILAT RAMADHAN DALAM MENINGKATKAN LITERASI KEAGAMAAN SISWA SEKOLAH DASAR - Rahmayanti, Riri; Septiana, Angelia; Adrias; Putri Zulkarnaini, Aissy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This studi aim to evaluate the effectiveness of the Ramadhan Pesantren Kilat program in improving the Religious Literacy of student at SDN 21 Kayu Aro, as well as to examine the sustainability of student’s practices after the program ends. Additionaly, this research also aims to assess the role of parents in supporting the continuity of religions learning at home. The method used in a qualitative approach with a desctiptive evaluative method, involving direct observation of students and teachers during the activities, as well as the involvement of parent in supporting students’ religious practices after the program conludes. The findings of thisstudy indicate that while the program successfully improved students’ understanding and practice of religious rituals, the sustainability of these habits after the program heavily depends on the support from parents. Therefore, active involvement of parents in this program is crucial to ensure that the relegious practices instilleed during Pesantren Kilat can be maintained in the long term and become part of students’ daiyi routines. The use of technologi-based learning media, differentiated approaches, and collaboration between schools and parents is necessary to improve the sustainability on the program.